Тенденції сучасної підготовки майбутніх учителів початкових класів - Біда Олена; Bida Olena; Гуттерер Єва; Hutterer Éva; Греба Ілдіко; Greba Ildikó (Видавництво «Код», 2023)
Резюме. Розглянуто методи і засоби які доцільно використовувати у процесі підготовки вчителя початкових класів. Наголошено на важливості використання в освітньому процесі групових форм роботи зі студентами. Відповідно до мети нової української школи конкретизуємо основні завдання формування педагогічної компетентності фахівця початкової освіти. Організацію процесу самоосвіти при підготовці фахівців показано як одним із головних чинників впливу на формування професійної компетентності вчителя. Під час розвитку системи освіти України пріоритетом є впровадження інформаційно-комунікаційних технологій, на що наголошено у статті. Розглянуто основні етапи професійного розвитку вчителя початкових класів.

Abstract. Competitiveness and professional competence of graduates of pedagogical specialties is the need of the hour. The methods and means that are expedient to use in the process of training primary school teachers are considered. The importance of using group forms of work with students in the educational process is emphasized. The cooperative learning method is singled out, taking into account the experience of the Singapore system. A special place in the educational process is given to the development of students’ research and creative skills. When training future primary school teachers, the importance of focusing on the main components of the Concept of the New Ukrainian School is emphasized. In accordance with the goal of the new Ukrainian school, we specify the main tasks of forming the pedagogical competence of a primary education specialist. The organizaƟ on of the process of self-educaƟ on during the training of specialists is shown to be one of the main factors infl uencing the formaƟ on of a teacher’s professional competence. During the development of the educaƟ on system of Ukraine, the priority is the introducƟ on of informaƟ on and communicaƟ on technologies, which is emphasized in the arƟ cle. The main stages of professional development of primary school teachers are considered. The methods and means that are expedient to use in the process of training primary school teachers are considered. The importance of using group forms of work with students in the educational process is emphasized. The cooperative learning method is singled out, taking into account the experience of the Singapore system. The importance of the professional standard «Teacher of primary classes of a general secondary education institution» is shown. In accordance with the goal of the new Ukrainian school, we specify the main tasks of forming the pedagogical competence of a primary education specialist. The organization of the process of self-education during the training of specialists is shown to be one of the main factors influencing the formation of a teacher’s professional competence. The main stages of professional development of primary school teachers are considered.
Tendencies of current training of future teachers of primary grades
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-4
Keywords: сучасна підготовка; майбутні фахівці; учителі початкових класів; професійний розвиток вчителя; педагогічна компетентність фахівця початкової освіти